DEEP BREATHING RELAXATION AND SANYINJIAO ACUPRESSURETHERAPY (SP6) AS A PAIN MANAGEMENT FOR PRIMARYDYSMENORRHEA IN ADOLESCENTS - Nugrahani, Cantika Iva; Christiana, Elisa; Khana, Fitri Hijri (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
Dysmenorrhea, or commonly known as menstrual pain, is a sensation of pain or abdominal cramps that occurs before and during the menstrual period. The use of drugs to reduce pain has negative side effects, so holistic care such as deep breathing relaxation techniques and acupressure therapy are one alternative to reduce dysmenorrhea pain. Deep breathing relaxation is a technique that involves slow and deep breathing to help reduce stress and anxiety (Trivia, 2021). While acupressure is a massage technique at certain points, proven to be effective in reducing menstrual pain. This type of research uses a Quasy Experiment design with a one group pretest and posttest design. The population in this study were all 2nd year female students of the Nursing Study Program at the Madura State Polytechnic. This study used purposive sampling, with the inclusion criteria of female adolescents aged 17-20 years, who had taken Holistic Care Medicine courses, experienced primary dysmenorrhea pain and did not use pharmacological therapy such as analgesics during the research data collection process. The exclusion criteria were having certain gynecological diseases or secondary dysmenorrhea and very severe pain levels. The sample in this study was 52 people. Data collection used a Visual Analog Scale measuring instrument with an intensity scale of 0-10 and a checklist of deep breathing relaxation therapy and SP6 acupressure techniques, data were processed computerized using SPSS software version 26. Univariate analysis used frequency distribution and bivariate analysis used the Wilcoxon test with a p-value <0.05. The results of the data distribution test obtained an abnormal data distribution, so it was continuedstatistical test using the Wilcoxon Test obtained a value of 0.000 (<0.05). Thus proving that the combination of deep breathing therapy and acupressure is effective in reducing primary dysmenorrhea pain in adolescents.